Asuhan Keperawatan Gerontik Pada Pasien Gout Arthritis Dengan Intervensi Pemberian Jus Nanas Untuk Menurunkan Kadar Asam Urat Di Panti Werdha Kasih Ayah Bunda Tangerang - Astuti Astuti; Siti Robeatul Adawiyah; Rina Puspita Sari; Siti Rahayu (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Gout or gout arthritis is a disease associated with high levels of uric acid in the blood. There are two ways to reduce uric acid, pharmacological and non-pharmacological. Non-pharmacological can be done by giving pineapple juice Pineapple has a very high vitamin C content, pineapple also has a very good vitamin C content. This vitamin works by helping the system associated with the kidneys to excrete more uric acid. Besides that, it is also useful for keeping purines from being produced into uric acid. Purpose: The purpose of this paper is to provide an overview of nursing care for gout arthritis patients in reducing uric acid levels by administering pineapple juice. Method: Case study design using nursing care. This case study sample used 1 patient who was intervened for 7 days. Results: based on the implementation results on Mr. J by applying pineapple juice for 7 days, data on uric acid levels were obtained in Mr. J on the third day it decreased from 8.3 mg/dl to 8.0 mg/dl and uric acid levels on the 7th day were 7.3 mg/dl. So that the diagnosis of health maintenance is not effectively resolved and it can be concluded that there is a change, this shows the effect of giving pineapple juice in reducing uric acid levels.